2016
DOI: 10.1136/tobaccocontrol-2016-053266
|View full text |Cite
|
Sign up to set email alerts
|

Educational and wealth inequalities in tobacco use among men and women in 54 low-income and middle-income countries

Abstract: Our results confirm that socioeconomic inequalities tobacco use exist in LMIC, varied widely between the countries and were much wider in the lowest income countries. These findings are important for better understanding and tackling of socioeconomic inequalities in health in LMIC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
48
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(54 citation statements)
references
References 41 publications
4
48
0
Order By: Relevance
“…This is consistent with previous findings indicating that low-income individuals experience increased PAH exposures related to poor air quality, which in turn is likely influenced by home location (i.e., proximity to industry or heavy traffic), and levels of environmental tobacco smoke [55]. It is important to note that smoking status may also be driving this relationship; higher smoking rates having been previously noted in low-income individuals relative to higher socioeconomic status individuals [56][57][58][59]. Indeed, careful scrutiny of the analysed data revealed nearly three times the number of non-smokers in households with incomes ≥$80,000 a year compared to those with incomes <$35,000 a year.…”
Section: Effects Of Demographic and Lifestyle Factorssupporting
confidence: 91%
“…This is consistent with previous findings indicating that low-income individuals experience increased PAH exposures related to poor air quality, which in turn is likely influenced by home location (i.e., proximity to industry or heavy traffic), and levels of environmental tobacco smoke [55]. It is important to note that smoking status may also be driving this relationship; higher smoking rates having been previously noted in low-income individuals relative to higher socioeconomic status individuals [56][57][58][59]. Indeed, careful scrutiny of the analysed data revealed nearly three times the number of non-smokers in households with incomes ≥$80,000 a year compared to those with incomes <$35,000 a year.…”
Section: Effects Of Demographic and Lifestyle Factorssupporting
confidence: 91%
“…Education is presumed to be an important determinant of an individual's tobacco-use behavior. The prevalence of tobacco use is inversely associated with an individual's level of education in LMICs (Bosdriesz, Mehmedovic, Witvliet, & Kunst, 2014;Palipudi et al, 2012;Sreeramareddy, Harper, & Ernstsen, 2018). This pattern is also evident in the findings of GATS and household income and expenditure survey of Pakistan in 2014.…”
Section: Study Purposementioning
confidence: 72%
“…This pattern of inequality in smoking has been extensively identified by studies in low-and middle-income countries, which have shown sociodemographic gradients in tobacco use. [25][26][27] For example, older smokers are more likely to quit 26,27 and education is inversely associated with smoking in multiple settings. 27 Evidence suggests that increasing tobacco price has the greatest potential to reduce socioeconomic disparities in smoking.…”
Section: Accepted Manuscriptmentioning
confidence: 99%